PENCIPTAAN BUKU ESAI FOTOGRAFI TOPENG DALANG SEBAGAI UPAYA MELESTARIKAN BUDAYA TRADISIONAL SUMENEP - Pratama, Rizky Julian; Bahruddin, Muh; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: Dalang mask has the sense of a traditional theater performing arts puppet resembling those in which each actor to use as a mask facepiece, and all the dialogue is controlled by the puppeteer. Shape mask performance Dalang in Sumenep very different from other traditional performing arts, which exist in the region Sumenep. In addition to the presentation using a mask (face cover), as well as the role of the puppeteer who controls all the players or props mask making art is different from other performing arts. In the village Slopeng, District Sumenep Dasuk there Dalang mask performing arts groups, which until today still exist and Functional in public life supporters, the group known as the